Canadian journal of Catholic history (Canadian Catholic Historical Association, 2024)
"The Canadian Journal of Catholic History is an annual peer-reviewed publication of the Canadian Catholic Historical Association. It publishes articles on the history of Catholicism in Canada as well as topics that have a connection to the Canadian Catholic experience. The journal also publishes historiographical articles that summarize and assess new trends and developments in Catholic history, as well as reviews of new books that significantly affect our understanding of Canadian Catholic history"